Interface Engineering in Organic Thin Film Transistors - Liguori, R.; Fusco, Sandra; Rubino, Alfredo; Usta, Hakan; Facchetti, A. F. (Institute of Electrical and Electronics Engineers Inc., 2017)
A novel semiconductor, the small molecule C6-NTTN, was used to fabricate organic thin film transistors (OTFTs). Different architectures and deposition techniques were employed, together with various surface treatments of the substrate, insulator and metal contacts, whose effect is analyzed through atomic force microscopy. The aim is to investigate the relationship between the process parameters and the electrical performance, with a particular attention to the quality of interfaces between active layers. The proportionality between the charge carrier mobility and the interface trap density was studied. © 2018 Elsevier B.V., All rights reserved.
Electron Devices Chapter (EDS); et al.; IEEE; IEEE - Electron Devices Society (EDS); IEEE -Romania Section; Ministry of Research and Innovation
Usta, Hakan/0000-0002-0618-1979; Liguori, Rosalba/0000-0002-0093-1169
Keywords: Organic Thin-Film Transistors (Otfts); Semiconductor-Insulator Interfaces; Semiconductor-Metal Interfaces; Trap-Limited Charge Transport; Atomic Force Microscopy; Interfaces (Materials); Thin Film Circuits; Thin Films; Transistors; Electrical Performance; Interface Engineering; Interface Trap Density; Organic Thin Film Transistor (Otfts); Organic Thin Film Transistors; Quality of Interfaces; Semiconductor-Insulator Interface; Semiconductor-Metal Interfaces; Thin Film Transistors